Prevalence and Associated Factors of Computer Vision Syndrome Among Academic Staff in the University of Gondar, Northwest Ethiopia: An Institution-Based Cross-Sectional Study - Amensisa Hailu Tesfaye; Mekuriaw Alemayehu; Giziew Abere; Tesfaye Hambisa Mekonnen (SAGE Publishing, 2022)
Introduction: Computer vision syndrome (CVS) is the leading occupational hazard of the 21st century, which causes the critical public health issues in the present era. In developing countries, including Ethiopia, data on the proportion and the causes of CVS are scarce among academic staff for policy conclusions. Accordingly, this study was conducted to determine the prevalence and factors associated with CVS among academic staff at the University of Gondar. Methods: Institution-based cross-sectional study design was conducted from March to April, 2021. A simple random sampling technique was used to select 525 study participants. Data were collected using a pre-tested self-administered structured questionnaire. The collected data were then entered into EpiData version 4.6 and analyzed using STATA version 14 software. The association between dependent and independent variables was computed with a binary logistic regression. Results: The prevalence of CVS was found to be 78.8% out of a total of 500 participants [95% CI (74.95, 82.30)], of which the majority (71.60%) of them were males. Using a computer for more than 9 years [AOR = 1.65, 95% CI (1.01, 2.71)], using visual display terminals [AOR = 2.63, 95% CI (1.60, 4.32)], and working in improper illumination levels (300 and >500 lux) [AOR = 2.47, 95% CI (1.47, 4.33)] increased the risk of CVS, whereas, Using eye droplets [AOR = 0.30, 95% CI (0.15, 0.58)] and taking rest breaks [AOR = 0.55, 95% CI (0.34-0.92)] were protective factors. Conclusion: This study disclosed that CVS was common among academicians. In the current study, the manifestation of CVS was affected by years of computer use, visual display terminals use, workplace illumination level, rest breaks, and eye droplets. Taking rest breaks in between the work, reducing exposure to display screens, use of eye drops, and optimizing workplace illumination levels are recommended to reduce the problem.